Effects of Elastic Band Exercise on Body Composition and and Cognitive-related Factors in Elderly Women - Chang-Gyun Kim (The Asian Journal of Kinesiology)
OBJECTIVES This study aimed to investigate the effects of an 8-week elastic band exercise program on body composition and cognitive-related factors in elderly women. METHODS Twenty-four healthy elderly women were randomly assigned to either an elastic band exercise group (EBG, n=12) or a control group (CG, n=12). Body composition and cognitive-related factors—specifically brain-derived neurotrophic factor (BDNF) and insulin-like growth factor-1 (IGF-1)—were assessed before and after the intervention. The exercise program was conducted three times per week, with each session lasting 50 minutes (10 minutes for warm-up, 30 minutes for the main exercise, and 10 minutes for cool-down). Blood samples were collected before and after the intervention to analyze IGF-1 and BDNF levels. Data were analyzed using independent t-tests, paired t-tests, and two-way repeated measures ANOVA, with statistical significance set at α=0.05. RESULTS Significant reductions were observed in body weight (BW) and body mass index (BMI) after the exercise intervention. In addition, both IGF-1 and BDNF levels showed significant increases following the 8-week program. However, no significant changes were found in muscle mass. CONCLUSIONS Elastic band exercise demonstrated positive effects on body weight, BMI, and cognitiverelated biomarkers (IGF-1, BDNF) in elderly women, although it did not significantly increase muscle mass. Considering its cost-effectiveness, accessibility, and safety, elastic band training is an appropriate exercise modality for older adults. Further research is needed to determine the effects of higher-intensity or longerduration programs on muscle mass development.